Exploring women’s pathways to civic leadership - Tolar, Mary Hale (Kansas State University, 2009)
Women leaders today have many sources to draw on for inspiration, motivation, and sustenance in their civic participation. Their participation is possible, in large part, because of generations of women who opened doors and broke down barriers. Women also face persistent barriers and challenges to leadership. What factors have influenced women, allowing them to move beyond historical limitations of participation to the exercise of leadership in the field of public service? This study employed qualitative research methods to explore women's pathways to civic leadership, focusing on women’s narratives using a collective case study design. The pathways explored in this study involve experiences and relationships that have led the subjects to, through, and away from service in the public sector. Cultural capital and social reproduction theory, with its focus on the individual’s dispositions and interactions with social institutions, was the framework used to explore the kinds of support, inputs or advantages women acknowledge as having an impact in their civic leadership. Female Truman Scholars, selected during their college years for their potential leadership in public service, formed the research population of the study. Respondents in this study, female Truman Scholars selected from 1977-1998, had at least ten years of education, career, and life experience from the time of selection. Themes that emerged from analysis of the data describe the impact of personal and family relationships, the role of mentoring, financial challenges and commitment to public service as critical experiences and relationships that both drive and impede respondents’ pathways. Respondents described personal and family relationships as inspirations and barriers; the presence of mentors as both a help and a hindrance, and the absence of mentors also as both benefit and deficit; meeting or succumbing to the financial challenges of public service careers; and finding their commitment to public service slip into disillusionment, or reinforced as a source that sustains. Findings related to the additive nature of gender roles to other challenges faced in public service leadership, the shadow-side of mentoring, and perseverance and disaffection related to one’s commitment to public service were informed by theory yet also highlight the complexity of women’s pathways.
Keywords: Women; Leadership; Public service; Education, Administration (0514)